Triterpenoid saponin-rich fraction of Centella asiatica decreases IL-1? and NF-?B, and augments tissue regeneration and excision wound repair - Mahmood, Amena; Tiwari, Ambrish K.; Şahin, Kazım; Küçük, Ömer; Ali, Shakir (Tubitak Scientific & Technological Research Council Turkey, 2016)
Wound healing is an orderly process driven by numerous cellular mediators that aim to accelerate it. In skin conditions such as leprosy and psoriasis, Centella asiatica, which contains high amounts of triterpenoid saponins (TSs), has been reported to have beneficial effects. This study examined the effects of TS fraction of the herb on tissue regeneration and excision wound repair in rat skin. Briefly, TS fraction was prepared from C. asiatica and applied on the wound area for 7 consecutive days. The IL-1 beta, NF-kappa B, and other biochemical parameters were then estimated, followed by examination of inflammatory cell infiltration, epithelialization, angiogenesis, and general morphology of granulation (wound) tissue by histopathology. Treatment decreased the IL-1 beta and NF-kappa B, increased epithelialization and collagen synthesis, and decreased matrix metalloproteinases. Asiatic acid, the active ingredient in the fraction, increased cell viability and inhibited nitrite production in macrophage culture. Taken together, TSs augmented wound healing, which could be due to their effect on cellular mediators involved in the process, thus creating a microenvironment that could promote tissue repair and favor tissue remodeling. The fraction, in addition to its effect on excision wounds in rat skin, is speculated to have a similar role in accidental, surgical, and diabetic wounds.
Keywords: Centella asiatica; triterpenoid saponins; wound healing; IL-1 beta; NF-kappa B; regeneration; repair